2009
DOI: 10.1590/s0100-29452009000400018
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do fruto de abacaxi comercializado pela Cooperfruto: Miranorte-TO

Abstract: Os produtores do estado do Tocantins estão tendo de manter ou melhorar o padrão de qualidade dos seus frutos, para garantirem uma boa comercialização. o trabalho objetivou avaliar a qualidade dos frutos de abacaxi comercializados na cooperativa Cooperfruto em Miranorte-TO, e verificar se estes se encontram dentro dos padrões mínimos exigidos para comercialização visando ao consumo in natura. a coleta de dados foi realizada no período de novembro de 2006 a maio de 2007, onde foram analisados mensalmente frutos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
(4 reference statements)
2
7
0
8
Order By: Relevance
“…The values calculated from floral induction to harvest time for the greenhouse cultivation are similar to those found for the same cultivar in the province of Paraná, Brazil, with 1.389,3 degree days in the same phenological period (Carvalho et al, 2005). The fruit sizes obtained at harvest in both cropping systems were lower than the crop's potential, according to Pereira et al(2009), who obtained fruit lengths with and without crown of 35,4 to 43,2 cm and 15,8 to 20,3 cm, respectively. This difference is due to the contribution of the crown to the fruit length, obtaining a relation of fruit length with crown/fruit length without crown of 1,89 in the greenhouse, whereas in those fruits cultivated in the field, this relation was of 3,01, which indicates a strong development of the crown under field conditions.…”
Section: Discussionsupporting
confidence: 74%
“…The values calculated from floral induction to harvest time for the greenhouse cultivation are similar to those found for the same cultivar in the province of Paraná, Brazil, with 1.389,3 degree days in the same phenological period (Carvalho et al, 2005). The fruit sizes obtained at harvest in both cropping systems were lower than the crop's potential, according to Pereira et al(2009), who obtained fruit lengths with and without crown of 35,4 to 43,2 cm and 15,8 to 20,3 cm, respectively. This difference is due to the contribution of the crown to the fruit length, obtaining a relation of fruit length with crown/fruit length without crown of 1,89 in the greenhouse, whereas in those fruits cultivated in the field, this relation was of 3,01, which indicates a strong development of the crown under field conditions.…”
Section: Discussionsupporting
confidence: 74%
“…This value is within the norms for classification of pineapple fruits, in which the fruit can be considered mature when SS is above 12.00 º Brix. This value of SS, according to Pereira et al (2009), is within the national values for good quality fruits for fresh consumption. Fig 5. 'Pérola' pineapple fruit characteristics in function of nitrogen (N) doses applied through fertigation: pH (A); titratable acidity (B) and ratio (SS/acid) (C).…”
Section: Resultssupporting
confidence: 51%
“…Comparing the different by-products, a significant difference (p < 0.05) was observed among the pH values (Table 2), with pineapple and melon by-products exhibiting the lowest and the highest values, respectively. Other studies that have used the edible parts of the fruits reported pH values for pineapple between 4.07 and 4.38 (Pereira et al, 2009); for apple, 3.70 to 3.88 (Fontes, Sarmento, Spoto, & Dias, 2008) and for melon, values between 5.01 and 6.95 (Aroucha et al, 2007). Such variations in pH are considered acceptable, since this parameter is associated with the process of fruit ripening and might present alterations according to the point of harvest (Pereira et al, 2009).…”
Section: Physicochemical Analysismentioning
confidence: 98%